Предмет: Алгебра,
автор: JuliaWoodsen
помогите пожалуйста решить с полным объяснением
Приложения:
Ответы
Автор ответа:
0
4^(2(x+1)^2)-2*4^(x(x+2)=1/2
4^(2x^2+2+4x)-2*4^(x^2+2x)=1/2
4^2*4^((x^2+2x)*2)-2*4^(x^2+2x)=1/2
4^(x^2+2x)=t
16t^2-2t-1/2=0
32t^2-4t-1=0
t=(2+-6)/32
t>0 по области значений
t=1/4
x^2+2x=-1
x^2+2x+1=0
(x+1)^2=0
x=-1
4^x(1+1/2)=3^x*sqrt(3)+3^x*sqrt(3)/3
4^x1,5=3^xsqrt(3)(1+1/3)
(4/3)^x=sqrt(3)*8/9
x=3/2
Похожие вопросы
Предмет: Математика,
автор: setrolena3649
Предмет: Қазақ тiлi,
автор: tbtb347
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: Викося